2005
DOI: 10.5558/tfc81675-5
|View full text |Cite
|
Sign up to set email alerts
|

Climate change impacts on drought-prone forests in western Canada

Abstract: From a climate change perspective, much of the recent international focus on forests has been on their role in taking up carbon dioxide (CO 2 ) from the atmosphere. The question of climate change impacts on forest productivity is also emerging as a critical issue, especially in drought-prone regions such as the western Canadian interior. Because of the complexity of interacting factors, there is uncertainty even in predicting the direction of change in the productivity of Canada's forests as a whole over the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(63 citation statements)
references
References 30 publications
3
60
0
Order By: Relevance
“…Projections of future climatic drying pose a major concern for Canada's boreal forest ecosystems (9), especially in the western Prairie Provinces where forest distribution and ecosystem functioning are strongly moisture limited (32). In many Canadian areas, the trends in forest growth were consistent with the directional trend in soil moisture ( Figs.…”
Section: Regional Variation In Growth Trends From Tree Rings Show Modsupporting
confidence: 56%
“…Projections of future climatic drying pose a major concern for Canada's boreal forest ecosystems (9), especially in the western Prairie Provinces where forest distribution and ecosystem functioning are strongly moisture limited (32). In many Canadian areas, the trends in forest growth were consistent with the directional trend in soil moisture ( Figs.…”
Section: Regional Variation In Growth Trends From Tree Rings Show Modsupporting
confidence: 56%
“…Most of the wood that will be harvested in Canada over the next 50 to 100 years will come from trees that are already growing or will be planted in the next decade with minimal climate change adaptation considerations. In some areas there will be an increase in forest productivity while in other areas there will be a decrease (Spittlehouse 2003, Hogg and Bernier 2005, Johnson and Williamson 2005. What will this mean for rotation ages, wood quality, wood volume, size of logs and determining the annual allowable cut?…”
Section: Adapting To Climate Change In Forestry -Challengesmentioning
confidence: 99%
“…Changes in temperature and precipitation regimes will mean that we will have to revise where and how planting stock and site preparation techniques are used. Species have a wide range of occurrence and it would be prudent to initially target areas near the edge of a species range where the earliest impacts are likely to occur (Hogg and Bernier 2005). In some cases we may have to return to existing second growth stands where the current regeneration is unacceptable as a source for the future forest and replant with other species or genotypes (Woods et al 2005).…”
Section: Adapting To Climate Change In Forestry -Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, at least once in the past, a climatic warming led to a very rapid transformation of the forest tundra to forest (MacDonald et al 1993). It has been suggested that forest stands, once established, do not much respond to small changes in climate, and that the bulk of the response to climate change may come in the form of regeneration failures or stand type changes following disturbances (Hogg 1997, Hogg and Schwarz 1997, Hogg and Bernier 2005. Poor regeneration of forest following fire has been observed along the southern boreal/grassland boundary (Hogg 1997) and in climatically dry areas of the southwestern Yukon (Hogg and Wein 2005).…”
Section: Impacts Of Climate Changementioning
confidence: 99%